2018
DOI: 10.1038/s41467-018-06428-2
|View full text |Cite
|
Sign up to set email alerts
|

Author Correction: Commensal microflora-induced T cell responses mediate progressive neurodegeneration in glaucoma

Abstract: The originally published version of this Article contained an error in Figure 4. The bar chart in panel f was inadvertently replaced with a duplicate of the bar chart in panel e. This error has now corrected in both the PDF and HTML versions of the Article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…In addition, it has been reported previously that endothelial cells of TM can secrete various factors and cytokines which play a pivotal role in regulation and modulation of ECM remodeling, and therefore affect the pathway of AH outflow (20,21). Most recently, specific HSP-T cell response has been reported to play a pivotal role in IOP-independent glaucoma progression (22). Therefore, we hypothesize that immune factors may be the cause rather than the result of glaucoma in SWS patients.…”
Section: Introductionmentioning
confidence: 83%
“…In addition, it has been reported previously that endothelial cells of TM can secrete various factors and cytokines which play a pivotal role in regulation and modulation of ECM remodeling, and therefore affect the pathway of AH outflow (20,21). Most recently, specific HSP-T cell response has been reported to play a pivotal role in IOP-independent glaucoma progression (22). Therefore, we hypothesize that immune factors may be the cause rather than the result of glaucoma in SWS patients.…”
Section: Introductionmentioning
confidence: 83%
“…In contrast to the innate immune system, the adaptive immune system requires up to 7 days to be activated. Recent report on the involvement of heat shock protein (HSP)-specific T cells offers the key evidence support a role for autoimmunity in glaucoma (30). However, analysis of T cells in patients and experimental models of glaucoma remains limited; there are only few studies focusing on the presence of specific T lymphocyte subsets in the sera of glaucoma patients.…”
Section: Involvement Of T Cells In Glaucomamentioning
confidence: 99%
“…In part, this is because pathogenic antigens in the retina are long thought to induce T regulatory (Treg) cells through a mechanism of ACAID, therefore maintaining the ocular immune privilege. Recent studies of the peripheral blood of glaucoma patients revealed that the immunity activated in glaucoma may not be counterbalanced by an efficient immune suppression (30,31). Patients with glaucoma exhibited a trend of decreased frequency of Treg and their CD4+ T cells presented a greater stimulation response characterized by increased proliferation and proinflammatory cytokine secretion.…”
Section: Involvement Of T Cells In Glaucomamentioning
confidence: 99%
See 2 more Smart Citations